Treatment of Acute Decompensated Chronic Heart Failure: Furosemide vs Furosemide and Metolazone: A Cross-Sectional Comparative Study - Risal, Ujjwol Prasad; Karki, Prahlad; Shah, Prashant (Nepalese Heart Journal, 2022)
Background: Heart failure is a leading cause of hospital admissions each year. In Nepal also the incidence of heart failure is increasing. Acute decompensated heart failure carries a poor prognosis. Most patients respond to intravenous loop diuretics but a substantial proportion of patients are resistant to them and may need additional diuretic agents like metolazone by the principle of “sequential nephron blockade”. Methods: In a hospital-based cross-sectional comparative study, we assigned 68 patients with acute decompensated chronic heart failure patients to receive furosemide at 1 mg/kg twice daily or furosemide at 1 mg/kg twice daily plus metolazone 5mg/day. The primary end-points were daily weight loss, negative water balance (difference between urine output and fluid intake) and symptomatic improvement on NYHA grading. Results: There were 55% males and 45% females in total. There was a significant difference (p-value =0.003) in mean weight loss observed between the two groups on day three, i.e., 0.971±0.6 kg and 1.5±0.78 kg in furosemide group and furosemide plus metolazone group respectively. Mean negative water significantly more in the combination group on day two (450±230.94 ml vs 750.59±416.92 ml) with p-value <0.001 and day three (780.88±352.48 ml vs 504.38±292.46 ml) with p-value 0.001. There was no significant change in symptoms on the basis of NYHA grading between the two groups, duration of hospital stay and adverse events like hypotension, acute kidney injury and dyselectrolytemia. Conclusion: Among patients with acute decompensated chronic heart failure, treatment with combination of furosemide and metolazone was found to be more effective than furosemide alone without significant increase in adverse effects.